Bambuphaga, a new bamboo feeding-leafhopper genus (Cicadellidae: Deltocephalinae: Punctulini) from India - Ramaiah, Mogili; Meshram, Naresh M.; Dey, Debjani (Zootaxa, 2023)
A new genus of bamboo feeding leafhopper, Bambuphaga n. gen. (Hemiptera: Cicadellidae: Delcephalinae) with Bambuphaga balajii n. sp. from India (Andhra Pradesh) as the type species is described, illustrated, placed in the tribe Punctulini and an annotated checklist to the tribe is provided. The type specimens and material examined are deposited in the National Pusa Collection (NPC), Indian Council of Agricultural Research-Indian Agricultural Research Institute (IARI), New Delhi, India.